The law of foreign contribution and foreign hospitality : the Foreign Contribution (Regulation) Act, 1976, Act 49 of 1976 / by P.C. Sharma and M. Kandasami. - Sharma, P. C. (Centre for Non-profits in India, 1995)
Commentary, includes text of the act.